PENGARUH KETERLIBATAN ORANGTUA DAN POLA ASUH TERHADAP DISIPLIN ANAK - Edy, Edy; CH, Myrnawati; Sumantri, Mohamad Syarif; Yetti, Elindra (Program Studi Magister Pendidikan Anak Usia Dini, 2018)
This study aims to obtain information about the influence of the Parent’s involvement in Family Education Program (PPK) and parenting styles to child discipline on PAUD student who already have an intervention of family education program. This study uses facto ex-post facto survey method. Respondence of this research are parents of PAUD student in south Jakarta who already have an intervention of family education program. Research Results (1) The involvement of parents at schools through family education programs has an impact on child development (discipline). (2) Parenting styles (democratic and authoritarian) have affects to discipline of children (3) Parental involvement at schools and parenting has interaction (4) Parental involvement in family education programs and democratic parenting have a better influence on child discipline (5) Active parental involvement in family education programs at schools and authoritarian parenting have an influence on children's discipline Keywords: Parents, Parenting Styles, and Child Discipline Penelitian ini bertujuan untuk mengetahui pengaruh keterlibatan orangtua dan pola asuh terhadap disiplin anak pada satuan PAUD yang sudah mendapatkan intervensi program pendidikan keluarga. Metode penelitian yang digunakan adalah survey expost facto. Responden penelitian adalah orang tua siswa PAUD di Jakarta Selatan setelah mendapatkan intervensi program pendidikan keluarga. Hasil penelitian menunjukkan bahwa (1) Keterlibatan orangtua di satuan pendidikan melalui program pendidikan keluarga memiliki pengaruh pada disiplin anak. (2) Pola asuh orangtua mempengaruhi disiplin anak (3) Keterlibatan orangtua di satuan pendidikan dan pola asuh memiliki interaksi (4) Keterlibatan orangtua pada program pendidikan keluarga dan pola asuh demokratis memiliki pengaruh lebih baik terhadap disiplin anak (5) Keterlibatan orangtua aktif pada program pendidikan keluarga dan pola asuh otoriter memiliki pengaruh terhadap disiplin anak. Kata Kunci: Orangtua. Pola Asuh, Disiplin Anak